2012
DOI: 10.1021/je201311n
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Extraction of Cyclic Polyhydroxy Carboxylic Acid Using Trioctylamine (TOA) in Different Diluents

Abstract: Quinic acid is a cyclic polyhydroxy carboxylic acid compound that is implicated in the perceived acidity of raw materials. It is a constituent of the tannins. In this work, the extraction of quinic acid was studied by using trioctylamine (TOA) with respect to the functional groups. The quinic acid extraction experiments employed TOA + solvent mixtures or pure solvent. The solvents included two acetates, two alcohols, and two ketones. The obtained experimental results of the extraction experiments are reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…However, in this study it can be clearly seen that the loading factors with all diluents decrease with the rise in DOA or TOPO concentration, and they become lower than unity in higher concentrations; so, overloading has not occurred. The same results ( Z > 1, low concentrations) are also revealed in different studies in the literature. , …”
Section: Resultssupporting
confidence: 86%
“…However, in this study it can be clearly seen that the loading factors with all diluents decrease with the rise in DOA or TOPO concentration, and they become lower than unity in higher concentrations; so, overloading has not occurred. The same results ( Z > 1, low concentrations) are also revealed in different studies in the literature. , …”
Section: Resultssupporting
confidence: 86%
“…The similar kind of behavior of toluene and xylene may be attributed to their close properties. Table shows the comparative study of reactive extraction of other carboxylic acids with tri- n -caprylyl amine in various diluents. Therefore, it was found that benzeneacetic acid has the highest distribution coefficient and extraction efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…MEK is a polar solvent and has a reactive functional group that upgrades the extraction capacity of the shaped acid–amine complex. The outcomes reveal that the increase in the starting amount of TPA in the organic media essentially improves the extraction yield of the process. , …”
Section: Results and Discussionmentioning
confidence: 96%